Land Routes in the Southern Cone of Colonial America - Lacoste, P (UNIV GRANADA, 2024)
Overland routes in the Southern Cone of America are examined in the context of the inter- modal system that was also articulated with maritime and fluvial routes. The Andes Mountain range was the frontier of land transportation means, with the predominance of road routes to the east and mule tracks to the west. In this context, specific historical subjects emerged, "troperos" in the River Plate-Pampean space, and "arrieros" in Chile and the mountain areas.